2021
DOI: 10.3390/medicina57070708
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Adnexal Pathology: Standardized Methods and Different Levels of Experience

Abstract: Background and objectives: An expert’s subjective assessment is still the most reliable evaluation of adnexal pathology, thus raising the need for methods less dependent on the examiner’s experience. The aim of this study was to evaluate the performance of standardized methods when applied by examiners with different levels of experience and to suggest the most suitable method for less-experienced gynecologists. Materials and methods: This single-center retrospective study included 50 cases of histologically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
5
1
Order By: Relevance
“…The sensitivity of subjective assessment in our study to detect malignant masses is 87.8% (78.4–97.2) which is similar to other studies in which the sensitivity of this approach ranged from 56.4% to 100% [ 7 , 9 ]. However, the specificity (69.1%) is lower than expected according to the literature (84.2–99.9%) [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The sensitivity of subjective assessment in our study to detect malignant masses is 87.8% (78.4–97.2) which is similar to other studies in which the sensitivity of this approach ranged from 56.4% to 100% [ 7 , 9 ]. However, the specificity (69.1%) is lower than expected according to the literature (84.2–99.9%) [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 88%
“…The sensitivity of subjective assessment in our study to detect malignant masses is 87.8% (78.4–97.2) which is similar to other studies in which the sensitivity of this approach ranged from 56.4% to 100% [ 7 , 9 ]. However, the specificity (69.1%) is lower than expected according to the literature (84.2–99.9%) [ 7 , 9 ]. This is probably because of a selection bias in our study since many of the adnexal lesions included had been classified as suspicious and required histological study, as evidenced by the high percentage of malignancy according to the pathological study (33.6%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For less experienced sonographers (less than 5 years of experience in gynecological ultrasound diagnosis), it is important to use objective methods to diagnose AMs [4]. Ultrasound-based diagnostic models and scoring systems [5][6][7][8] can be used to predict the malignancy of AMs to help inexperienced sonographers in the diagnosis of AMs. A commonly used diagnostic model is the Risk of Malignancy Index (RMI) [9], which is a risk index calculated based on serum CA125, menopausal status, and ultrasound characteristics to identify benign and malignant AMs, and is currently recommended by many national for AMs properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that a US study undertaken by an experienced sonographer (Subjective Assessment) is the best choice for classifying adnexal masses [2][3][4]. However, other US scores have been developed to help non-expert sonographers to classify adnexal masses such as IOTA Simple Rules Risk Assessment (2016), available as a digital version of the IOTA Simple Rules (2008) [5], which predicts the risk of malignancy in an online calculator [6]; the ADNEX model (Assessment of Different Neoplasia in the Adnexa) (2014) [7] with or without CA125; or the O-RADS system (Ovarian Adnexal Reporting and Data System) [8], introduced in 2020 by the American College of Radiology (ACR) [9] with an updated version in November 2022, which classifies adnexal masses into five categories according to lexicon descriptors and includes management options.…”
Section: Introductionmentioning
confidence: 99%